Peran Persembahan dalam Pengelolaan Keuangan pada Organisasi Nirlaba : Studi Kasus Gereja Kristen Jawi Wetan Jember - Sherlina Annundi, Angelin; Ahmad, Arisona (Universitas Katolik Widya Karya Malang, 2025)
This research aims to discover the role of offerings in the financial management of nonprofit organizations, namely the Church. This research uses descriptive qualitative methods. Data collection methods used are direct interviews and documentation at one of the nonprofit-oriented entities. The data analysis techniques used are data reduction, data presentation, and conclusion drawing. This study's results explain that offerings play an important role in the financial management of nonprofit organizations where the object used is the Church. Offerings also have many types, but the financial statements made are still single-entry or simple bookkeeping.